Update on systemic prostate cancer therapies: management of metastatic castration-resistant prostate cancer in the era of precision oncology - Nuhn, Philipp; Grilli, Maurizio (European urology, 2019)
Context - Introduction of novel agents for the management of advanced prostate cancer provides a range of treatment options with notable benefits for men with metastatic castration-resistant prostate cancer (mCRPC). At the same time, understanding of optimal patient selection, effective sequential use, and development of resistance patterns remains incomplete. - Objective - To review current systemic therapies and recent advances in drug development for mCRPC and strategies to aid in patient selection and optimal sequencing. - Evidence acquisition - A literature review of PubMed/Medline, Cochrane Library, Current Contents Medicine, Web of Science, Clinical Trial.Gov, WHO-ICTRP (January 2004-November 2017), and the proceedings of major international meetings (2015/2016/2017) was performed in November 2017. - Evidence synthesis - In the last few years, several new options for treatment of mCRPC have shown a survival benefit in phase III trials besides docetaxel:abiraterone, enzalutamide, cabazitaxel, radium-223, and sipuleucel-T. Radium-223 and denosumab have increased options in management of bone metastases. Currently, novel agents such as next-generation androgen receptor (AR) axis-targeting treatments, immunotherapeutics, or therapies targeting other oncogenic and genomic pathways, particularly poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors and PD-1 inhibitors, are under clinical investigation. With increasing treatment options for mCRPC, information on how to personalize management and how to select and sequence existing therapies is beginning to emerge, as are predictive biomarkers (homologous repair mutations, mismatch repair mutations, AR splice variant 7). Finally, early use of active agents in the castration-sensitive state will likely also change the clinical management of the disease when it becomes castrate resistant. - Conclusions - The emergence of new drugs for mCRPC has improved treatment options dramatically. Currently, systemic treatment options for mCRPC include hormonal therapy, chemotherapy, immunotherapy, and radionuclide therapy as well as bone-modifying agents and palliative or supportive measures. Further, new genetically targeted agents (PARP inhibitors and PD-1 inhibitors) are on the horizon for certain subsets of biomarker-selected patients. The best strategies for patient selection and optimal sequential use to achieve the longest cumulative survival improvement and to prevent early resistance remain unclear. - Patient summary - The current literature and proceedings from relevant congresses related to available systemic agents for the treatment of metastatic castration-resistant prostate cancer, including novel genetically targeted therapies, including poly(adenosine diphosphate-ribose) polymerase inhibitors and PD-1 inhibitors, were reviewed. Current therapies and ongoing developments are discussed.